A DETERMINISTIC APPROACH FOR SOLVING THE HULL AND WHITE INTEREST RATE MODEL - Chen, Homing; Hu, Cheng-Feng (Taiwanese journal of mathematics, 2011)
This work considers the resolution of the Hull and White interest rate model. A deterministic process is adopted to model the random behavior of interest rate variation as a deterministic perturbation. It shows that the interest rate function and the yield function of the Hull and White interest rate model can be obtained by solving a nonlinear semi-infinite programming problem. A relaxed cutting plane algorithm is then proposed for the resulting optimization problem. The features of the proposed method are tested using a set of real data and compared with some commonly used spline fitting methods. 2000Mathematics Subject Classification: Primary 62P05; Secondary 46N10. Key words and phrases: Semi-infinite programming, Hull and White, Interest rate model.